Evaluasi Pengaruh Antara Pendapatan Desa dan Belanja Desa di Kecamatan Purwoasri Tahun 2020-2024 - Faris Aji Vagood Lucky; Hestin Sri Widiawati; Linawati Linawati (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to explore the impact of PADes, ADD, and DD on village expenditures in Purwoasri District from 2020 to 2024. A quantitative approach with a causal type was used in this research. Data were gathered from the Village Budget (APBDes) realization reports of ten selected villages, using the Probability Sampling technique. The analysis employed multiple linear regression, testing classical assumptions such as normality, multicollinearity, autocorrelation, and heteroscedasticity. The study's findings indicate that, individually, Village-Generated Revenue (PADes), Village Fund Allocation (ADD), and Village Funds (DD) significantly influence village expenditures. When considered together, these three independent variables also have a significant impact on village expenditures. These results highlight that PADes, ADD, and DD are crucial in determining the direction and magnitude of village expenditures. By effectively managing these resources, villages can better allocate funds and ensure the sustainability of financial management. The study concludes that these revenue sources play a vital role in shaping village financial planning, supporting development projects, and improving public services. It also suggests that the district government should continue enhancing its financial management practices to further optimize the use of these funds for village development.